Pencil, paper and stars the handbook of traditional and emergency navigation - Buchan, Alastair (John Wiley & Sons, 2008)
Electronic navigation systems are extremely reliable but when they do fail onboard repair at sea is rarely possible. Also, their operation depends on a continuous supply of electricity. Should this fail they will stop and unexpectedly lacking the means of position finding, chart plotting and route planning how can the modern navigator continue their passage in a safe and seamanlike manner? This user friendly book gives simple, practical, get-you-home navigation techniques, which can be used if electronic navigation systems aboard a yacht fail.